Analisa Laju Korosi Material Stainless Steel Grade SS304 dan Alloy UNS N08020 Terhadap Asam Sulfat dan Natrium Hidroksida - Meryanalinda; Agus Setiyo Umartono; Deddy Setiawan (Wahana Teknik, 2020)
Corrosion is a process of degradation metal quality. Its process will decrease the properties of a metal due to a chemical reaction between a metal or alloy with its environment. This research aims at investigating the corrosion rate of SS304 and UNS N08020 alloy in sulfuric acid solution and sodium hydroxide solution. In this study, the samples of SS304 and UNS N08020 alloy are immersed for 49 days in different solution. The method for calculate the corrosion rate is the weight loss method. The results of the corrosion rate test carried out for 49 days and the weight of the material was weighed once every 1 week, the value of the SS304 grade stainless steel material with battery water immersion media was 5.6439653 mm/y, on the SS304 grade stainless steel material with soda solution dipping media fire is 0.0075844 mm/y, on UNS N08020 alloy material with battery water immersion media is 0.0179111 mm/y, on UNS N08020 alloy material with caustic soda solution immersion media is 0.0082329 mm/y. Corrosion that occurs in each material is pitting corrosion. Keywords: corrosion, loss, pitting, rate, SS304, UNS N08020, weight.